Crowds and Popular Power: Reading Elias Canetti in Caracas - Samet, Robert (Social research, 2023)
There are strong continuities between crowd theory, which flowered during the early twentieth century, and theories of populist mobilization. Elias Canetti's Crowds and Power (1960) bridges these two literatures. Canetti gives us two relatively underappreciated ideas—the sting of command and the impulse for survival—that explain how populist movements change over time. To demonstrate how Canetti's work speaks to theories of populism, I draw on my fieldwork in Caracas, Venezuela. Venezuela's Bolivarian Revolution was, arguably, the most progressive political movement of the twenty-first century, but it veered wildly off course. Crowd theory gives us tools to track this transformation. Rather than imagining that populist movements are vacuous from the outset, Canetti directs attention toward their animating grievances. This article considers how the grievances that fed the Bolivarian Revolution eventually consumed it; this is a modest attempt to understand how one of the most promising political movements in recent memory ended up such a long way from where it started.